Lexical analysis of the Code of Medical Ethics of the Federal Council of Medicine - Andrade Jr.,Edson de Oliveira (2016)
Summary Introduction: The Code of Medical Ethics (CME) of the Federal Council of Medicine is the legal document that exposes the moral discourse of Brazilian physicians to society and the profession. It is a set of propositions based on which doctors say they are committed to values of conduct aimed at fair and proper professional practice. Objectives: To verify through lexical analysis of the CME corpus if the goals presented in the arguments of the resolution that established the code are properly addressed in these regulations. Methods: This is a quantitative and qualitative study of descriptive nature, aiming at a lexical analysis of the CME. The lexical analysis was performed using a method of Top-Down Hierarchical Classification of vocabulary, as described by Reinert in 1987, assuming that words used in similar contexts are associated with a single lexical world. In addition to the analysis of results, an improved representation of the charts related with Factorial and Similitude Analyses was made. Results: Six clusters were extracted, leading to the identification of three major branches: health care, professional practice and research. These branches revolve around the figures of physician and patient. The similitude analysis revealed a complementarity status between these two figures. Conclusion: The lexical analysis showed that the purposes contained in the resolution that established the CME were adequately represented in the document body.